2003
DOI: 10.1023/a:1024927711913
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We developed and described a new approach to vital analysis of functional activity of multidrug resistance markers (ABC transporters) in intact biopsy specimens from human solid tumors by the method of flow cytofluorometry. The algorithm of the study underwent revision, and the cell suspension was obtained in the final stage. Intensification of intracellular doxorubicin accumulation (fluorescence) and increase in the number of fluorescent cells and total fluorescence of doxorubicin-accumulating cells produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[36,37] It is found that PEG can reduce the surface tension, prevent silver volume nucleation, and help to fill the narrow trenches. [38] German et al [39] mentioned that liquid can not only generate a rearrangement torque to bring flat surface into contact, but also induce a capillary force to accelerate diffusion and rearrangement of metal particles. Fouad et al [40] employed PEG as a main reducing agent and PVP as a capping and dispersing agent to synthesize metal conductive nanopigments.…”
Section: Discussionmentioning
confidence: 99%
“…[36,37] It is found that PEG can reduce the surface tension, prevent silver volume nucleation, and help to fill the narrow trenches. [38] German et al [39] mentioned that liquid can not only generate a rearrangement torque to bring flat surface into contact, but also induce a capillary force to accelerate diffusion and rearrangement of metal particles. Fouad et al [40] employed PEG as a main reducing agent and PVP as a capping and dispersing agent to synthesize metal conductive nanopigments.…”
Section: Discussionmentioning
confidence: 99%
“…Functional activity of ABCtransporters was estimated by flow cytometry procedure adapted for studying solid tissues [6].…”
mentioning
confidence: 99%